Reachability Problems 8th International Workshop, RP 2014, Oxford, UK, September 22-24, 2014, Proceedings - Ouaknine, Joel; Potapov, Igor; Worrell, James (Theoretical Computer Science and General Issues,, 2014)
This book constitutes the proceedings of the 8th International Workshop on Reachability Problems, RP 2014, held in Oxford, UK, in September 2014. The 17 papers presented in this volume were carefully reviewed and selected from 25 submissions. The book also contains a paper summarizing the invited talk. The papers offer new approaches for the modelling and analysis of computational processes by combining mathematical, algorithmic, and computational techniques.